Pengaruh Workshop & FGD Mechanical Design Terhadap Keberminatan Menggunakan Software Gambar Pada Siswa SMK Bidang Teknik Mechanical - Oscar, Oscar Haris; Agus Wibowo; Sandya Gilang Samudra; Amirin (Universitas Nusa Putra & Persatuan Insinyur Indonesia, 2025)
Mechanical Design in general has the meaning of mechanical design using design software, the ability of Mechanial Design students is very limited, this is due to the resources of tools and people, FGD and workshop activities will help students improve their software design skills so that this will have a positive impact on the interest of vocational students in the field of Mechanical Design, the method used in this activity is the workshop method, FGD and questionnaire, after this activity is carried out, the results of student interest are quite high in the field of Mechanical Design, This is indicated by the results of activities in the form of questionnaires to 36 participants, obtained results as many as 100% of 36 students who stated the importance of Mechanical Design, before the community service activities were carried out there were students who assessed themselves with the highest ability of 9 students (25%) determining their ability assessment at 7, while after the workshop and FGD activities this resulted in an increase in student ability, namely the highest of 16 students (44%) determining their ability assessment at 8.